ANALISIS TINGKAT ADOPSI PETANI DENGAN PENDEKATAN PTT PADI DI DESA BUNGARAYA KECAMATAN BUNGARAYA KABUPATEN SIAK - Rizqi Sari Anggraini; Jakoni Jakoni (DINAMIKA PERTANIAN, 2013)
Integrated Plant Management Approach as a national program must be applied on the rice production centers. One of rice production center in Riau Province is Bunga Raya District, Siak Regency. In 2010, the cultivated area of rice in the district was 8,546 ha with total production of about 21,083 MT/ha. The aim of this research was to know the adoption level of integrated plant management of paddy filed by farmers. The research was conducted in Bungaraya Village, Bungaraya District, Siak Regency from January to December 2011. The measurement of adoption level and dissimination impct of integrated plant management for paddy included farmer identity, technology componen of integrated plant management for paddy, farmer response level, and feedback. The results show that the level of farmer adoption of technology componen for integrated plant management was reletively high, ranging from 82 – 100%. The integrated plant management approach increased rice productivity from 3.4 MT/ha to 5 – 6 MT/ha. Therefore, Bunga Raya as rice barn of Siak Regency which is begun from increasing planted area and cropping index of rice from Regency government.